Does pre-existing aortic regurgitation protect from death in patients who develop paravalvular leak after TAVI?. (15th April 2017) - Colli, Andrea; Besola, Laura; Salizzoni, Stefano; Gregori, Dario; Tarantini, Giuseppe; Agrifoglio, Marco; Chieffo, Alaide; Regesta, Tommaso; Gabbieri, Davide; Saia, Francesco; Tamburino, Corrado; Ribichini, Flavio; et al.
Abstract: Objective: The aim of this study was to investigate interactions among pre-procedural aortic regurgitation (AR), post-procedural paravalvular leak (PVL) and long-term clinical outcomes. Methods and results: We analyzed data prospectively collected in the Italian Transcatheter balloon-Expandable Registry (ITER) on aortic stenosis (AS) patients. The degree of pre-procedural AR and post-procedural PVL was stratified as: absent/trivial, mild, and moderate/severe. VARC definitions were applied to outcomes. Of 1708 patients, preoperatively, AR was absent/trivial in 40% of the patients, mild in 42%, and moderate in 18%. Postoperatively, PVL was moderate–severe in 5%, mild in 32% of patients, and absent/trivial in 63%. Clinical follow-up, median 821 days (IQR 585.75), was performed in 99.7% of patients. PVL, but not preoperative AR, was a major predictor of adverse outcome (HR 1.33, CI 95% 0.9–2.05, p  = 0.012 for mild PVL, HR 1.36, CI 95% 0.9–2.05, p  < 0.001 for PVL ≥ moderate and OR 1.04, p  = 0.97 respectively). Patients with moderate–severe PVL and preoperative left ventricle (LV) dilatation (LVEDVi > 75 ml/m 2 ) showed better survival than those without dilatation (HR 8.63, p  = 0.001). Conclusions: In patients with severe AS treated with balloon-expandable TAVI, the presence of PVL, but not pre-procedural AR, was a major predictor of adverse outcome. Preoperative LV dilatation seemed to offer some clinical advantages.